Does Manufacturing Sophistication Lead to Higher Demand for Vocational Workers? Evidence from Indonesia - Wicaksono, Padang; Priyadi, Lionel (Economics and Finance in Indonesia, 2018)
Indonesia post-crisis manufacturing growth has been dominated by technologically sophisticated industry. Hypothetically, this development would increase the demand for skilled and more specialized workers like vocational school graduates. However, statistical evidences show that manufacturing sophistication stimulated by integration with the Global Production Network increase demand for vocational as well as general high school graduates. Moreover, higher demand does not necessarily result in sustainable career prospect, as many vocational graduates still have limited opportunity to improve their skills while climbing the seniority ladder possibly caused by shifting Global Value Chain from export-oriented toward domestic market-oriented that affect the industry's technological complexity.